Polyhydroxyalkanoate beads as a particulate vaccine against Streptococcus pneumoniae and Neisseria meningitidis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Microbiology at Massey University, Manawatu, New Zealand - González Miró, Majela (Massey University, 2017)
Streptococcus pneumoniae and Neisseria meningitidis are the major causes of pneumonia and meningitis, respectively, worldwide. Capsular polysaccharide-protein vaccines (conjugate vaccines) provide protection against these diseases but not protection against infections caused by serotypes and serogroups not included in these vaccines. Proteins have been increasingly considered as antigens for vaccine development due to their more structurally conserved composition when compared to capsular polysaccharides. Proteins subunit vaccines are safe and protective; however, they have limitations such as serotype-dependent immunity, and low immunogenicity of the proteins, requiring adjuvant to be included in these formulations or delivery systems that enhance the desired immune response. In addition, complex production procedures are required, increasing production costs and therefore market prices making these vaccines inaccessible for many people affected by these diseases. Recently, bacterial storage polymer inclusions have been developed as protein antigen carriers. Polyhydroxyalkanoate, in particular 3-polyhydroxybutyrate (PHB) inclusions have been successfully bioengineered to display antigens from pathogens like Mycobacterium tuberculosis and Hepatitis C virus. These particulate vaccine candidates elicited both a Th1 and Th2 immunity patterns combined with a protective immune response against Mycobacterium bovis in mice. This thesis focuses on the study of polyhydroxybutyrate (PHB) beads properties as a carrier/delivery system engineered to display antigens from extracellular bacteria. The antigens Pneumococcal adhesin A, Pneumolysin (proteins) and 19F capsular polysaccharide (CPS) from Streptococcus pneumoniae, and Neisserial adhesin A, factor H binding protein (proteins) and serogroup C CPS from Neisseria meningitidis were displayed on the PHB bead surface. These antigenic proteins were produced as fusion proteins on the PHB bead surface, while the CPS was covalently attached by chemical conjugation. Mice vaccinated with these PHB beads produced strong and antigen-specific antibody levels. In addition, splenocytes from the same mice generated both IL-17A and IFN-ɣ production. The antibodies elicited against antigenic pneumococcal proteins were able to recognise the same protein in the context of an Streptococcus pneumoniae whole cell lysate from more than six different strains, while antibodies produced after vaccination with 19F CPS conjugate to PHB showed high opsonophagocytic titers against the homologous strain. In the case of Neisseria meningitidis, bactericidal antibodies were elicited in mice vaccinated with PHB beads displaying proteinaceous and CPS antigens. Overall, this thesis shows that PHB as particulate vaccine candidate holds the promise of a broadly protective vaccine that can be produced cost-effectively for widespread application to prevent diseases caused by Neisseria meningitidis and Streptococcus pneumoniae.
Listed in 2018 Dean's List of Exceptional Theses
Keywords: Vaccines; Biotechnology; Streptococcus pneumoniae; Neisseria meningitidis; Dean's List of Exceptional Theses